ANALISIS KEGIATAN ARISAN DALAM PERSPEKTIF ISLAM DI DESA WIRINGTASI PINRANG - Sukasi, Lilis (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Arisan is an activity that is often held by the community, which many of it are Muslims. Arisan activity is also an economic activity that contains akad-akad (Islamic legal contract) in it. So the purpose of this study is to examine the activities of arisan in Wiringtasi Pinrang in the perspective of Islam This research uses descriptive qualitative method that aims to understand the activity of arisan in Wiringtasi Pinrang. From the results of the research it can be summarized that the trading activities in the Wiringtasi do not form any association, and the arisan itself still contains elements of usury from "the cost of 0" and loans with additional interest. Because many of arisan user do not know the economic contract according to Islamic law. keywords : arisan in Islamic perspective, buy and sell in arisan, savings and loan of arisan.